PENGARUH CULTURALLY RESPONSIVE TEACHING (CRT) BERBANTU MEDIA KOMIK DIGITAL TERHADAP KECERDASAN EMOSIONAL SISWA SD - Utami, Safina Dwi; Prastyo, Danang; Hanindita, Amelia Widya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research investigates the impact of Culturally Responsive Teaching (CRT) supported by a digital comic on emotional intelligence among third-grade students at SDN Dr. Sutomo V/327 Surabaya. The study background reveals students’ low emotional intelligence, evidenced by limited skills in emotion regulation, teamwork, and empathy. Employing a quantitative method with a quasi eksperimental equivalent posttest only control group design. The sample includes 54 students, with 27 students in the experimental class receiving CRT instruction assisted by a digital comic and 27 students in the control class receiving contextual instruction assisted by PowerPoint. The instrument, an emotional intelligence assessment, measures five aspects, namely self awareness, self regulation, self motivation, emphaty, dan social skills. Following normality and homogeneity tests, data analysis via t test yielded significant differences in posttest emotional intelligence scores between experimental and control class (sig. < 0,05). These findings confirm that CRT integrated with a digital comic in the experimental class significantly enchances third grade students emotional intelligence. The study recommends using the CRT approach assisted by a digital comic to develop students’ affective aspects and as an alternative, contextual, engaging, and meaningful teaching strategy.